NH3-SCR (selective catalytic reduction) catalyst as well as preparation method and application thereof

By loading Cu and Ce onto high-silica LTA molecular sieves, stable CuOx clusters and Ce-O-Si bridging structures are formed, solving the problem of insufficient low-temperature activity and high-temperature stability of Cu-based catalysts in diesel vehicle exhaust treatment. This achieves efficient NOx conversion and anti-poisoning ability, making it suitable for diesel vehicle exhaust denitrification.

CN121402137APending Publication Date: 2026-01-27GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511555816.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing Cu-based NH3-SCR catalysts for diesel vehicle exhaust treatment suffer from the problem of balancing low-temperature activity and high-temperature hydrothermal stability, and are susceptible to sulfur and phosphorus poisoning and carbon deposit deactivation, resulting in insufficient application stability.

Method used

High-silica LTA molecular sieves are used as a support, and Cu and rare earth metal element Ce are combined to load active components through impregnation and ion exchange methods to form CuOx clusters and Ce-O-Si bridging structures, thereby improving the high-temperature hydrothermal stability and anti-poisoning ability of the catalyst.

Benefits of technology

It maintains a 90% NOx conversion rate and a 95% N2 selectivity within the temperature range of 230~550℃, exhibiting excellent high-temperature hydrothermal stability and anti-poisoning performance, and is suitable for diesel vehicle exhaust denitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121402137A_ABST
    Figure CN121402137A_ABST
Patent Text Reader

Abstract

The invention provides an NH3-SCR catalyst and a preparation method and application thereof, the NH3-SCR catalyst comprises an LTA molecular sieve and active components loaded on the LTA molecular sieve, and the active components comprise Cu and rare earth metal elements. According to the invention, the LTA molecular sieve and the double active components composed of Cu and rare earth metal elements have a synergistic effect, so that the catalyst shows efficient NH3-SCR catalytic activity and excellent high-temperature hydrothermal stability, and when the catalyst is applied to an NH3-SCR reaction, 90% of NOx conversion rate can be maintained at 230-550 DEG C, and 90% of N2 selectivity can be maintained at the same time. The catalyst is used in the field of diesel vehicle tail gas denitration, can realize high-efficiency treatment of tail gas NOx, and accords with corresponding emission standard limits.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of catalysis, and relates to an NH3-SCR catalyst and a preparation method and application thereof. BACKGROUND

[0002] Diesel vehicle exhaust is the main emission source of nitrogen oxides (NO x , including NO, NO2, N2O), and strict emission standards have been implemented worldwide. Given that internal combustion engines will still dominate the diesel transportation field in the coming decades, it is crucial to continuously develop advanced NO x x control technologies. In exhaust aftertreatment technology, NH3 selective catalytic reduction (NH3-SCR) has become the most effective solution. SCR catalysts need to maintain stable purification efficiency under extreme temperature conditions (low-temperature cold start <225°C to high-temperature regeneration >900°C) of diesel exhaust systems, so developing catalysts with wide temperature window and high and low temperature activity has become a core requirement.

[0003] Zeolite-based catalysts dominate current NH3-SCR research, among which small-pore zeolites such as Cu-SSZ-13 that meet the national VI standard perform outstandingly, with an activity window of 200-550°C, >98% nitrogen selectivity, and excellent hydrothermal stability. However, the high-temperature hydrothermal aging (HTA, such as 900°C / 10%H2O) generated during the diesel particulate filter (DPF) regeneration process exposes the defects of existing systems: Cu-SSZ-13 exhibits relatively high NO x conversion efficiency in the low-temperature section (175-225°C), but the CHA cage structure is prone to dealumination and Cu species sintering under high-temperature hydrothermal conditions, resulting in a sharp decline in activity after HTA; Cu-ZSM-5 improves certain thermal stability through ten-membered ring pore channel structure, but it is difficult to meet the high conversion demand in the 175-225°C low-temperature section due to insufficient Cu 2+ ion exchange sites—both cannot break the performance trade-off between “low-temperature conversion efficiency and high-temperature hydrothermal tolerance”, i.e., improving one side performance at the expense of the other.

[0004] More severely, the inevitable sulfur (SO x ) and phosphorus (PO4 3- ) impurities in diesel vehicle exhaust will strongly interact with catalyst active sites, forming stable sulfide or phosphate species, resulting in permanent poisoning of active sites; at the same time, unburned hydrocarbons in the exhaust are prone to deposit in the catalyst pores to form carbon deposits, blocking the diffusion channels of reactants, further exacerbating catalyst deactivation.

[0005] This performance compromise, superimposed with sulfur and phosphorus poisoning and carbon deposition deactivation, makes it difficult for existing Cu-based catalysts to adapt to the complex operating conditions of diesel vehicles for a long time, which seriously restricts the application stability of NH3-SCR technology. Therefore, the development of a new generation of NH3-SCR catalysts that take into account high-efficiency low-temperature activity, excellent high-temperature hydrothermal stability, and resistance to poisoning and carbon deposition has become an urgent need in the industry. SUMMARY

[0006] In view of the deficiencies in the prior art, the purpose of the present application is to provide a NH3-SCR catalyst and its preparation method and application. In the present application, the synergistic effect of LTA molecular sieve and the dual active component composed of Cu and rare earth metal elements makes the catalyst exhibit high-efficiency NH3-SCR catalytic activity and excellent high-temperature hydrothermal stability. When applied to NH3-SCR reaction, it can maintain 90% NO x conversion rate and 90% N2 selectivity at 230-550℃. In the field of diesel vehicle exhaust denitration, it can achieve efficient treatment of exhaust NO x , meeting the corresponding emission standard limits.

[0007] To achieve this purpose, the present application adopts the following technical solutions:

[0008] In a first aspect, the present application provides a NH3-SCR catalyst, which comprises an LTA molecular sieve and an active component supported on the LTA molecular sieve, the active component comprising Cu and a rare earth metal element.

[0009] The NH3-SCR catalyst according to the present application is a transition metal-based catalyst with high-silicon LTA molecular sieve as the carrier. The high-silicon LTA molecular sieve belongs to a three-dimensional microporous molecular sieve with LTA topological configuration. The molecular sieve has tetramic ring, hexameric ring and octameric ring as basic ring structural units, and the framework is composed of two independent cage structures: one is sod cage (cansoapstone cage) with structure symbol [4 6 6 8 ], and the other is LTA cage with structure symbol [4 12 6 8 8 6 ]; adjacent sod cages are connected to each other through double tetramic rings (d4r), and then form LTA cages to finally build a regular three-dimensional pore system. This specific pore structure determines its good application prospect in the field of NH3-SCR.

[0010] In the catalyst provided by the present application, copper mainly occupies the charge compensation site of single / double aluminum center in the LTA molecular sieve, forming (CuOH) + -Z and Cu 2+ -2Z species (Z represents Al 3+substitution (to counteract the resulting skeletal negative charge). The key finding is that under HTA conditions (750-900°C) that simulate DPF regeneration, the active copper species evolve: (1) (CuOH) + - Z aggregate into CuO confined to zeolite pores x clusters; (2) Cu in sod cages + migrate to single six-rings (s6r) and oxidize to stable Cu 2+ s6r sites. In contrast to the CHA structure of SSZ-13, the confined channels of LTA make CuO x form two morphologies - highly dispersed sub-nanoclusters and bulk crystals, governed by aggregation kinetics.

[0011] Advanced characterization techniques were used to resolve the atomic-level interactions between rare earth elements and the LTA framework. Taking the rare earth element Ce as an example, it was found that: (1) Ce 3+ / Ce 4+ redox pairs (CuOH) + - Z species have a stabilizing effect, which can inhibit their high-temperature agglomeration into CuO x clusters; (2) the Ce-O-Si bridging effect will have an impact on the retention of Bronsted acid sites; (3) the LTA topology ([4 6 6 8 ] sod cages connected by d4r) has a spatial confinement effect on CeO x phases, which can delay the collapse of the framework.

[0012] The following are preferred technical solutions of the present application, but not as a limitation on the technical solutions provided by the present application. Through the following preferred technical solutions, the technical purposes and beneficial effects of the present application can be better achieved and realized.

[0013] Preferably, the rare earth metal element includes any one of Ce, Y, La, Pr, Nd, Sm, Gd or Yb or a combination of at least two of them, and is further preferably Ce.

[0014] Preferably, the Si / Al ratio of the LTA molecular sieve is 9-30, such as 9, 10, 12, 15, 18, 20, 23, 25, 28 or 30, etc.

[0015] Preferably, the loading amount of Cu on the LTA molecular sieve is 0.5wt%-3.5wt%, such as 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% or 3.5wt%, etc.

[0016] Preferably, the loading amount of the rare earth metal element on the LTA molecular sieve is 0.5wt%-10.5wt%, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or 10.5wt%, etc.

[0017] Preferably, the mass ratio of the Cu and the rare earth metal element is 1:(0.5-4), for example, 1:0.5, 1:1, 1:2, 1:3 or 1:4, etc.

[0018] Preferably, the average particle size of the NH3-SCR catalyst is 2.5-3.5μm, for example, 2.5μm, 2.6μm, 2.8μm, 3μm, 3.2μm or 3.5μm, etc.

[0019] In a second aspect, the present application provides a preparation method of the NH3-SCR catalyst according to the first aspect, which comprises: first preparing an LTA molecular sieve, and then loading active components on the LTA molecular sieve by an impregnation method and / or an ion exchange method to obtain the NH3-SCR catalyst.

[0020] The preparation method provided by the present application realizes efficient synthesis of the catalyst, and the final product has excellent NH3-SCR activity and high-temperature hydrothermal stability.

[0021] Preferably, the preparation method of the LTA molecular sieve comprises a dry gel hydrothermal synthesis method.

[0022] The synthesis method of the LTA molecular sieve according to the present application is a dry gel assisted solvothermal method. The synthesis yield of this method is much higher than that of the ordinary solvothermal method. After synthesis, the molecular sieve only needs to be calcined to directly load the metal without ammonium exchange, which simplifies the synthesis steps of the final catalyst, reduces the industrial production steps and energy loss, and conforms to the concept of green chemical synthesis. Moreover, the molecular sieve prepared by this method has good NH3-SCR catalytic activity and N2 selectivity after loading the double active components, and shows good hydrothermal stability and high space velocity resistance.

[0023] Preferably, the dry gel hydrothermal synthesis method comprises: mixing a silicon source, an aluminum source and an aqueous solution of an organic template agent, reacting, removing part of the liquid in the system after the reaction is completed, obtaining a sol product, mixing with HF to perform an aging reaction, obtaining a gel, and obtaining the LTA molecular sieve after crystallization and calcination.

[0024] It can be understood that the wooden mortar can be used for mixing when mixing HF.

[0025] Preferably, the organic template includes a benzimidazole analogue and tetramethylammonium hydroxide (TMAOH).

[0026] Preferably, the benzimidazole analogue includes 1,2-dimethyl-3-(4-methylbenzyl)imidazole hydroxide 1 or 1,2-dimethyl-3-(2-fluorobenzyl)imidazole hydroxide 1, and is further preferably 1,2-dimethyl-3-(4-methylbenzyl)imidazole hydroxide 1 (12DM3(4MB)IOH).

[0027] The present application uses benzimidazole analogues as the template for the crystallization reaction. Such organic compounds all contain a cyclic structure and have a moderate molecular size, and can play a structure-directing and filling role in the synthesis of LTA molecular sieves. In addition, such organic compounds are all charged in aqueous solution, and play a charge-filling role in the synthesis of LTA molecular sieves.

[0028] Preferably, the silicon source includes silica sol and / or tetraethyl orthosilicate, and is further preferably tetraethyl orthosilicate.

[0029] Preferably, the aluminum source includes any one or a combination of at least two of aluminum hydroxide, pseudo-boehmite or aluminum sulfate, and is further preferably aluminum hydroxide.

[0030] Preferably, the copper source includes any one or a combination of at least two of anhydrous copper acetate, copper nitrate pentahydrate, copper sulfate or copper chloride, and is further preferably anhydrous copper acetate.

[0031] Preferably, the cerium source includes any one or a combination of at least two of ammonium cerium sulfate, cerium sulfate, cerium diphenylglycolate, cerium iodate, cerium peroxide, cerium dioxide or cerium nitrate, and is further preferably cerium nitrate.

[0032] Preferably, the process of mixing the aqueous solution of the silicon source, the aluminum source and the organic template includes first dissolving the aluminum source with the aqueous solution of the benzimidazole analogue, and then sequentially adding the tetramethylammonium hydroxide and the silicon source.

[0033] Preferably, the sol product includes the benzimidazole analogue, the tetramethylammonium hydroxide, the silicon oxide, the aluminum oxide and the water.

[0034] Preferably, in the sol product, the molar ratio of the silicon oxide to the aluminum oxide is 9-30, such as 9, 10, 12, 15, 18, 20, 30, etc.

[0035] In the present application, by controlling the ratio of the raw material silicon source and the aluminum source, LTA molecular sieves with different silicon-aluminum ratios can be synthesized.

[0036] Preferably, the molar ratio of the benzimidazole analog, tetramethylammonium hydroxide, silicon oxide, aluminum oxide and water in the sol product is 1:(0.02-0.14):(1.5-2.5):(0.002-0.16):(9-11), such as 1:0.02:1.5:0.002:4, 1:0.05:1.5:0.002:9, 1:0.07:1.8:0.005:9.5, 1:0.1:2:0.01:10, 1:0.1:2:0.066:10, 1:0.12:2.2:0.013:1 or 0.5, 1:0.14:2.5:0.016:11, etc.

[0037] In the present application, after mixing the silicon source, aluminum source and organic template (benzimidazole analog, tetramethylammonium hydroxide) in proper proportions, all the ethanol and appropriate amount of water generated by hydrolysis are evaporated to make the water content of the target product meet the above-mentioned molar ratio; the amount of tetramethylammonium hydroxide and aluminum oxide can be changed according to the silicon-aluminum ratio of the LTA molecular sieve to be synthesized. The product obtained under the above-mentioned proportion has a very wide crystallization window, and the LTA molecular sieve prepared therefrom has very excellent hydrothermal stability.

[0038] Preferably, the mass ratio of the HF to the benzimidazole analog in the sol product is (0.9-1.1):1, such as 0.9:1, 1:1 or 1.1:1, etc.

[0039] Preferably, the crystallized product is sequentially separated, washed and dried before the calcination.

[0040] Preferably, the separation and washing method comprises negative pressure suction filtration.

[0041] Preferably, the solvent for the washing is water and ethanol.

[0042] Preferably, the drying temperature is 80-140℃, such as 80℃, 90℃, 100℃, 120℃ or 140℃, etc.

[0043] Preferably, the drying time is 1-24h, further preferably 21-24h, such as 1h, 5h, 10h, 15h, 20h, 21h, 22h, 23h or 24h, etc.

[0044] Preferably, the crystallization is carried out in a rotating sealed hydrothermal kettle.

[0045] Preferably, the crystallization temperature is 120-180℃, such as 120℃, 130℃, 140℃, 150℃, 160℃, 170℃ or 180℃, etc.

[0046] Preferably, the crystallization time is 8h~4d, such as 8h, 12h, 1d, 2d, 3d or 4d, etc.

[0047] Preferably, the calcination temperature is 550℃~700℃, such as 550℃, 600℃, 650℃ or 700℃, etc.

[0048] Preferably, the calcination holding time is 4h~10h, such as 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.

[0049] Preferably, the calcination heating rate is 1℃ / min~5℃ / min, such as 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min, etc.

[0050] Preferably, the active component is loaded simultaneously or sequentially by impregnation method; or, the active component is loaded simultaneously or sequentially by ion exchange method; or, the active component is loaded sequentially by impregnation method and ion exchange method; or, the active component is loaded sequentially by ion exchange method and impregnation method.

[0051] Preferably, the active component is loaded sequentially in the order of Cu first and rare earth metal element second, and further preferably, the active component is loaded sequentially in the order of Cu by ion exchange method first and rare earth metal element by impregnation method second.

[0052] In the present application, the active component is loaded sequentially in the order of Cu by ion exchange method first and rare earth metal element by impregnation method second, which is the optimal choice in terms of comprehensive catalytic performance and loading content control. Taking the rare earth metal element Ce as an example, if the active component is loaded sequentially in the order of Ce by impregnation method first and Cu by ion exchange method second, it is difficult to control the content of Cu, and it is even more difficult to make the content of Cu reach a suitable content range; if the active component is loaded simultaneously by impregnation method, Cu may form large particles of CuO, which will have a negative effect on catalytic activity; and if the active component is loaded simultaneously by ion exchange method, it will be difficult to load Ce to a suitable high content.

[0053] Preferably, the impregnation method is initial wet impregnation method.

[0054] Preferably, the preparation method of the hydroxyl type 1, 2-dimethyl 3-(4-methylbenzyl) imidazole comprises: mixing 1, 2-dimethyl imidazole and α-chloro-p-xylene and a second solvent, and sequentially performing reflux reaction, recrystallization reaction and ion exchange reaction to obtain the hydroxyl type 1, 2-dimethyl 3-(4-methylbenzyl) imidazole.

[0055] Preferably, the second solvent comprises chloroform.

[0056] Preferably, the reflux reaction is performed under stirring.

[0057] Preferably, the temperature of the refluxing reaction is 24-36℃, such as 24℃, 25℃, 27℃, 30℃, 32℃, 35℃ or 37℃, etc.

[0058] Preferably, the time of the refluxing reaction is 24-72h, such as 24h, 30h, 40h, 48h, 60h, 70h or 72h, etc.

[0059] Preferably, the method of the recrystallization reaction comprises: performing rotary evaporation on the product obtained from the refluxing reaction, adding a third solvent for recrystallization reaction after removing the second solvent, and performing solid-liquid separation after the reaction is completed to obtain a recrystallization product.

[0060] Preferably, the method of the solid-liquid separation comprises suction filtration.

[0061] Preferably, the product after the suction filtration is sequentially subjected to washing and vacuum drying, and the solvent for the washing is diethyl ether.

[0062] Preferably, the third solvent comprises methanol and / or diethyl ether, and further preferably comprises methanol and diethyl ether.

[0063] In the present application, the recrystallization effect is best when the third solvent is a mixture of methanol and diethyl ether, wherein the methanol functions to dissolve the raw material and the diethyl ether functions to recrystallize.

[0064] Preferably, the product obtained from the refluxing reaction is sequentially subjected to suction filtration and centrifugal separation before the rotary evaporation.

[0065] Preferably, the method of the ion exchange reaction comprises: dispersing the recrystallization product in water, and performing ion exchange reaction with a hydrogen-oxygen type cation resin to obtain the hydrogen-oxygen type 1, 2-dimethyl 3-(4-methylbenzyl) imidazole.

[0066] Preferably, the ion exchange reaction is performed twice.

[0067] Preferably, the time of each ion exchange reaction is 20-30h, such as 20h, 22h, 25h, 28h or 30h, etc.

[0068] In a third aspect, the present application also provides an application of the NH3-SCR catalyst as described in the first aspect or prepared by the preparation method as described in the second aspect, and the application comprises removing nitrogen oxides in fixed source flue gas and / or mobile source tail gas.

[0069] The numerical ranges recited in the present application include not only the point values recited but also the range values between the recited point values. Due to the consideration of the length and simplicity, the present application does not list the specific point values included in the range.

[0070] Compared with the prior art, the application has the following beneficial effects:

[0071] (1) The NH3-SCR catalyst has high NO x removal rate and N2 selectivity, and is especially suitable for NO x removal at high space velocity. -1 The NH3-SCR catalyst has a NO x removal rate of more than 90% at a space velocity of 100,000 h x and a temperature range of 225℃~500℃, and has a N2 selectivity of more than 95% at a temperature range of 200℃~550℃.

[0072] (2) The preparation process of the NH3-SCR catalyst mixes a silicon source, an aluminum source, an organic template agent and HF to obtain LTA molecular sieve by one-step method, and then loads Cu and rare earth metal by a post-loading method, so that the preparation process is simple, clean and efficient. x The NH3-SCR catalyst has excellent hydrothermal stability, and compared with a fresh catalyst, the NO x removal rate of the NH3-SCR catalyst decreases by ≤10% at a temperature range of 250℃~500℃ after hydrothermal aging treatment at 900℃ for 16h, and the N2 selectivity decreases by ≤2% at a temperature range of 200℃~550℃, so that the NH3-SCR catalyst is suitable for diesel vehicle exhaust aftertreatment system. BRIEF DESCRIPTION OF DRAWINGS

[0073] Figure 1 is an XRD graph of the fresh NH3-SCR catalyst provided in Example 1.

[0074] Figure 2 is a BET graph of the fresh NH3-SCR catalyst provided in Example 1.

[0075] Figure 3 is a SEM graph of the fresh NH3-SCR catalyst provided in Example 1.

[0076] Figure 4 is a NO x conversion rate graph of the fresh NH3-SCR catalyst provided in Example 1, Example 13-Example 15.

[0077] Figure 5 is a NO x conversion rate graph of the fresh NH3-SCR catalyst provided in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0078] The technical solutions of the present application will be further illustrated by specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present application, and should not be regarded as specific limitations on the present application.

[0079] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application; the terms "comprising" and "having," and any variations thereof, as used herein are intended to cover a non-exclusive inclusion.

[0080] It should be noted that the 12DM3(4MB)IOH used in the following examples and comparative examples is prepared by the following method:

[0081] 1. Mix 0.10 mol of 1,2-Dimethylimidazole and 0.10 mol of 4-Methylbenzyl chloride (a-Chloro-p-xylene), continuously stir at room temperature for 48 h to obtain a white suspension. Transfer the suspension to a rotary evaporator, evaporate at 303 K under reduced pressure for 0.5 h until the suspension becomes a white solid powder. Increase the temperature to 333 K, continue to evaporate under reduced pressure until the white powder is completely dried. Dissolve the powder in methanol, add 400 ml of ether under vigorous stirring for recrystallization. The product is suction filtered, and eluted with 100 mL of ether (or ethyl acetate) three times, evaporate at 303 K under reduced pressure for 30 min, then continue to evaporate at 363 K under reduced pressure until completely dry. The white solid product obtained at this time is 1,2-Dimethyl-3-(4-methylbenzyl)imidazolium chloride (12DM3(4MB)ICl).

[0082] 2. Dissolve the 12DM3(4MB)ICl solid powder in deionized water, add an appropriate amount of Amberlite IRN-78 anion exchange resin, continuously stir at room temperature for 48 h to exchange Cl - to OH completely - . Suction filter the mixture, recover the anion exchange resin and collect the liquid product to obtain a 12DM3(4MB)IOH aqueous solution. Evaporate and concentrate the solution at 353 K to obtain a 12DM3(4MB)IOH aqueous solution with an appropriate concentration.

[0083] 3. Use phenolphthalein as an indicator, and titrate the product solution with 0.1 mol / L dilute hydrochloric acid to determine the true concentration of 12DM3(4MB)IOH.

[0084] Example 1

[0085] The present example provides an NH3-SCR catalyst, comprising an LTA molecular sieve and dual active components Cu and Ce supported on the LTA molecular sieve, wherein the mass percentage content of Cu is 2.0 wt%, the mass percentage content of Ce is 3.2 wt%, and Si / Al is 15.

[0086] The preparation method is as follows:

[0087] (1) Al(OH)3 is dissolved in a certain amount of 12DM3(4MB)IOH aqueous solution, continuously stirred for 1 h to make it fully dissolved. Then TMAOH is added, and stirring is continued for 3 h. To the above mixture, tetraethyl orthosilicate (TEOS) is added, and TEOS is fully hydrolyzed by vigorous stirring for 16 h. It is heated to 360 K, and under the condition of continuous stirring, all the ethanol and a proper amount of water generated by hydrolysis are evaporated to make the water content of the target product meet the chemical composition of the sol (0.50 12DM3(4MB)IOH:0.05TMAOH:1.00SiO2:0.033Al2O3:5.00H2O). The sol is transferred to a fume hood, and a proper amount of hydrofluoric acid (HF) (12DM3(4MB)IOH:HF=1:1) is added using a pipette, stirred uniformly, and a solid product is obtained.

[0088] Finally, it is transferred to a hydrothermal kettle, sealed, and placed in an oven at 448 K, and crystallized for 24 h under the condition of continuous rotation. The hydrothermal synthesis product is taken out, placed in a 500 mL beaker, 300 mL of deionized water is added, stirred uniformly, and then left to stand for 3 h. Then, it is suction filtered, washed with a large amount of deionized water, the solid product is collected, and dried for 12 h under ventilation. The sample solid powder is placed in a muffle furnace, heated to 873 K at a heating rate of 1 ℃ / min, and calcined for 8 h to completely remove the residual organic structure directing agent (OSDA), and an LTA molecular sieve is obtained.

[0089] (2) Cu is loaded by ion exchange method using a certain concentration of copper acetate solution, dried at 373 K for 16 h, calcined at 873 K for 6 h, then Ce is loaded by impregnation method using a certain concentration of cerium nitrate solution, and dried and calcined in the same way to obtain the NH3-SCR catalyst.

[0090] Example 2

[0091] The present example provides an NH3-SCR catalyst, comprising an LTA molecular sieve and dual active components Cu and Ce supported on the LTA molecular sieve, wherein the mass percentage content of Cu is 2.0 wt%, the mass percentage content of Ce is 3.2 wt%, and Si / Al is 9.

[0092] The preparation method is as follows:

[0093] (1) Al(OH)3 was dissolved in a certain amount of 12DM3(4MB)IOH aqueous solution, and continuously stirred for 1 h to make it fully dissolved. Then TMAOH was added, and stirring was continued for 3 h. To the above mixture, tetraethyl orthosilicate (TEOS) was added, and TEOS was fully hydrolyzed by stirring vigorously for 16 h. It was heated to 360 K, and all the ethanol and a certain amount of water generated by hydrolysis were evaporated under the condition of continuous stirring, so that the water content of the target product met the chemical composition of the sol (0.50 12DM3(4MB)IOH:0.05TMAOH:1.00SiO2:0.055Al2O3:5.00H2O). The sol was transferred to a fume hood, and a certain amount of hydrofluoric acid (HF) (12DM3(4MB)IOH:HF = 1:1) was added using a pipette, and stirred uniformly to obtain a solid product.

[0094] Finally, it was transferred to an autoclave, sealed, and placed in an oven at 393 K, and crystallized for 4 d under the condition of continuous rotation. The hydrothermal synthesis product was taken out, placed in a 500 mL beaker, 300 mL of deionized water was added, stirred uniformly, and then left to stand for 3 h. Then, it was suction filtered, washed with a large amount of deionized water, and the solid product was collected and dried under ventilation for 12 h. Then, the sample solid powder was placed in a muffle furnace, heated to 823 K at a heating rate of 3 ℃ / min, and calcined for 10 h to completely remove the residual organic structure directing agent (OSDA), to obtain an LTA molecular sieve.

[0095] (2) Cu was loaded by ion exchange method using a certain concentration of copper acetate solution, dried at 373 K for 16 h, calcined at 873 K for 6 h, then Ce was loaded by impregnation method using a certain concentration of cerium nitrate solution, and dried and calcined in the same way to obtain the NH3-SCR catalyst.

[0096] Example 3

[0097] The present embodiment provides an NH3-SCR catalyst, comprising an LTA molecular sieve and a dual active component Cu and Ce loaded on the LTA molecular sieve, wherein the mass percentage content of Cu is 2.0 wt%, the mass percentage content of Ce is 3.2 wt%, and Si / Al is 30.

[0098] The preparation method is as follows:

[0099] (1) Dissolve Al(OH)3 in an appropriate amount (depending on the concentration) of 12DM3(4MB)IOH aqueous solution and stir continuously for 1 h to ensure complete dissolution. Then add TMAOH and continue stirring for 3 h. Add tetraethyl orthosilicate (TEOS) to the above mixture and stir vigorously for 16 h to ensure complete hydrolysis of TEOS. Heat the mixture to 360 K and evaporate all the ethanol and an appropriate amount of water generated by hydrolysis under continuous stirring to make the water content of the target product conform to the chemical composition of the sol (0.50 12DM3(4MB)IOH:0.05TMAOH:1.00SiO2:0.0167Al2O3:5.00H2O). Transfer the sol to a fume hood and add an appropriate amount of hydrofluoric acid (HF) (12DM3(4MB)IOH:HF=1:1) using a pipette, stir evenly, and obtain a solid product.

[0100] Finally, the product was transferred to a hydrothermal reactor, sealed, and placed in an oven at 453 K for crystallization under continuous rotation for 8 hours. The hydrothermal synthesis product was then removed, placed in a 500 mL beaker, and 300 mL of deionized water was added. After stirring thoroughly, the mixture was allowed to stand for 3 hours. Subsequently, it was filtered, washed with a large amount of deionized water, and the solid product was collected. After drying under ventilation for 12 hours, the sample solid powder was placed in a muffle furnace and heated to 973 K at a heating rate of 5 °C / min for 4 hours to completely remove residual organic structure-directing agent (OSDA), yielding LTA molecular sieve.

[0101] (2) Using a copper acetate solution of a certain concentration, Cu is loaded by ion exchange. The mixture is first dried at 373K for 16h and then calcined at 873K for 6h. Then, Ce is loaded by impregnation using a cerium nitrate solution of a certain concentration. The mixture is dried and calcined in the same way to obtain the NH3-SCR catalyst.

[0102] Example 4

[0103] The difference between this embodiment and Example 1 is that the mass percentage of Ce in the NH3-SCR catalyst is 0.3wt%, and the concentration of the cerium nitrate solution is adaptively adjusted in step (2).

[0104] All other preparation methods and parameters are consistent with those in Example 1.

[0105] Example 5

[0106] The difference between this embodiment and Example 1 is that the mass percentage of Ce in the NH3-SCR catalyst is 1.2 wt%, and the concentration of the cerium nitrate solution is adaptively adjusted in step (2).

[0107] All other preparation methods and parameters are consistent with those in Example 1.

[0108] Example 6

[0109] The difference between this embodiment and Example 1 is that the mass percentage of Ce in the NH3-SCR catalyst is 7.5 wt%, and the concentration of the cerium nitrate solution is adaptively adjusted in step (2).

[0110] All other preparation methods and parameters are consistent with those in Example 1.

[0111] Example 7

[0112] The difference between this embodiment and Example 1 is that the mass percentage of Ce in the NH3-SCR catalyst is 10.5 wt%, and the concentration of the cerium nitrate solution is adaptively adjusted in step (2).

[0113] All other preparation methods and parameters are consistent with those in Example 1.

[0114] Example 8

[0115] The difference between this embodiment and Example 1 is that the mass percentage of Cu in the NH3-SCR catalyst is 0.5wt%, and the concentration of the copper nitrate solution is adaptively adjusted in step (2).

[0116] The remaining preparation methods and parameters are consistent with those in Example 1.

[0117] Example 9

[0118] The difference between this embodiment and Example 1 is that the mass percentage of Cu in the NH3-SCR catalyst is 3.5 wt%, and the concentration of copper nitrate solution is adaptively adjusted in step (2).

[0119] The remaining preparation methods and parameters are consistent with those in Example 1.

[0120] Example 10

[0121] The difference between this embodiment and Example 1 is that the mass percentage of Cu in the NH3-SCR catalyst is 0.2wt%, and the concentration of copper nitrate solution is adaptively adjusted in step (2).

[0122] The remaining preparation methods and parameters are consistent with those in Example 1.

[0123] Example 11

[0124] The difference between this embodiment and Example 1 is that the Si / Al ratio of the LTA molecular sieve is 50, and in step (1), the sol is made to conform to the chemical composition of (0.50 12DM3(4MB)IOH:0.05TMAOH:1.00SiO2:0.01Al2O3:5.00H2O).

[0125] The remaining preparation methods and parameters are consistent with those in Example 1.

[0126] Example 12

[0127] The difference between this embodiment and Example 1 is that the dual active components loaded on the LTA molecular sieve are Cu and La, and the cerium nitrate solution is replaced with lanthanum nitrate solution in step (2).

[0128] The remaining preparation methods and parameters are consistent with those in Example 1.

[0129] Example 13

[0130] The difference between this embodiment and embodiment 1 is that in step (2), Ce is first loaded by impregnation with a certain concentration of cerium nitrate solution, dried at 373K for 16 hours, and then calcined at 873K for 6 hours. Then Cu is loaded by ion exchange with a certain concentration of copper acetate solution, and dried and calcined in the same way.

[0131] All other preparation methods and parameters are consistent with those in Example 1.

[0132] Example 14

[0133] The difference between this embodiment and Example 1 is that the mass percentage of Ce in the NH3-SCR catalyst is 0.5wt%. In step (2), Cu and Ce are simultaneously loaded by ion exchange using a certain concentration of cerium nitrate solution and copper acetate solution. The catalyst is first dried at 373K for 16h and then calcined at 873K for 6h.

[0134] All other preparation methods and parameters are consistent with those in Example 1.

[0135] Example 15

[0136] The difference between this embodiment and embodiment 1 is that in step (2), Cu and Ce are simultaneously loaded by impregnation using a certain concentration of cerium nitrate solution and copper acetate solution, dried at 373K for 16h, and then calcined at 873K for 6h.

[0137] All other preparation methods and parameters are consistent with those in Example 1.

[0138] Comparative Example 1

[0139] The difference between this comparative example and Example 1 is that the NH3-SCR catalyst does not include the active component Ce, and Ce loading is not performed in step (2).

[0140] All other preparation methods and parameters are consistent with those in Example 1.

[0141] Comparative Example 2

[0142] The difference between this comparative example and Example 1 is that the NH3-SCR catalyst does not include the active component Cu, and Cu loading is not performed in step (2).

[0143] All other preparation methods and parameters are consistent with those in Example 1.

[0144] Comparative Example 3

[0145] The difference between this comparative example and Example 1 is that the molecular sieve in the NH3-SCR catalyst is SSZ-13 molecular sieve, and step (1) is not performed. In step (2), Cu and Ce are loaded sequentially on the SSZ-13 molecular sieve.

[0146] All other preparation methods and parameters are consistent with those in Example 1.

[0147] Performance testing

[0148] The fresh catalyst prepared in Example 1 was subjected to XRD, BET, and SEM tests, and the results are as follows: Figures 1-3 As shown.

[0149] The NH3-SCR catalyst powders prepared in Examples 1-15 and Comparative Examples 1-3 were compressed, ground, and sieved. Samples of 40-60 mesh particles were placed in a quartz tube, and the NO content before and after hydrothermal aging treatment of the catalyst was tested in a fixed-bed reactor. x Removal rate and N2 selectivity, the test results are shown in Table 1. Figure 4 and Figure 5 As shown.

[0150] The conditions for hydrothermal aging treatment were as follows: containing 10% H2O, with air as the carrier gas, an air flow rate of 200 mL / min, corresponding to an aging amount of 200 mg of catalyst, and hydrothermal aging treatment temperatures of 850℃, 900℃, and 950℃, with a hydrothermal aging treatment time of 16 h.

[0151] NO x Test conditions for removal rate and N2 selectivity: [NO] = [NH3] = 500 ppm, [O2] = [H2O] = 5%, N2 as the equilibrium gas, total reaction gas flow rate of 500 mL / min, reaction temperature range of 150℃-550℃, reaction time of 1 h at each temperature until equilibrium is reached. Concentrations of reactants NH3 and NO, and byproducts NO2 and N2O were measured using a Thermo IS50 infrared spectroscopy device; catalyst dosage corresponded to a space velocity of 100,000 h⁻¹. -1 .

[0152] It is understandable that T in Table 1 50 T 90 They refer to NO respectively xThe temperatures required to achieve removal rates of 50% and 90%.

[0153] Table 1

[0154]

[0155] This invention prepared a series of dual-active-component NH3-SCR catalysts via a sequential synthesis strategy and systematically investigated the regulatory mechanism of rare earth metals (especially Ce) on the catalytic performance of NH3-SCR. Furthermore, an ion exchange method was used in NH4+... + A 2wt% copper loading (Cu / Al=0.35) was achieved on the -LTA precursor, balancing the contradiction between the accelerated deactivation caused by high copper content (e.g., Cu / Al=0.5) and the limitation of loading by nitrate exchange. Subsequently, a gradient of cerium (0.5-10.5wt%) was precisely introduced via initial wet impregnation to construct a Ce-modified system without disturbing the copper distribution. The Cu-LTA matrix, with its superior hydrothermal stability compared to Cu-SSZ-13 and Cu-ZSM-5, effectively isolated the specific effects of Ce, simultaneously improving the catalyst's hydrothermal stability (resistance to 900°C / 10% H2O aging), low-temperature activity (175-225°C), and resistance to sulfur, phosphorus, and carbon poisoning.

[0156] The XRD pattern of the NH3-SCR catalyst prepared in Example 1 is shown below. Figure 1 As shown in the figure, the product prepared in Example 1 has an LTA configuration, and its diffraction peak positions all correspond to the standard characteristic peaks of LTA configuration molecular sieves; the BET plot of Example 1 is shown in the figure. Figure 2 As shown, the catalyst has a high specific surface area; the SEM image of Example 1 is shown below. Figure 3 As shown, the catalyst is roughly cubic in shape with a particle size of 3 μm.

[0157] Combined with Example 1 in Table 1 and Comparative Examples 1-3 Figure 5 It is evident that in this invention, LTA molecular sieve, Cu, and rare earth metal elements work synergistically and are all indispensable. In Comparative Example 2, the lack of Cu loading resulted in the catalyst failing to achieve a 90% conversion rate after aging; while in Comparative Example 3, replacing LTA with SSZ-13 led to a sharp decline in catalyst performance after aging, preventing the catalyst from reaching a 50% conversion rate.

[0158] A comparison of the data from Example 1 and Examples 4-10 in Table 1 shows that the mass content of Ce and Cu in the catalyst affects the performance of the catalyst. In the above examples, the best effect is achieved when the content of Cu is 2.0 wt% and the content of Ce is 3.2 wt%. A comparison of the data from Example 1 and Example 11 in Table 1 shows that when the silica-alumina ratio of the LTA molecular sieve is not within the preferred range, the performance of the catalyst will also decrease. A comparison of the data from Example 1 and Example 12 in Table 1 shows that among all rare earth metal elements, Ce and Cu can achieve the greatest synergistic effect and have the most significant improvement on catalyst performance.

[0159] A comparison of the data from Example 1 and Examples 13-15 in Table 1 Figure 4 It is understood that in this invention, the loading order of the two active components also affects the performance of the catalyst. Using ion exchange to load Cu and then using impregnation to load rare earth metals is the optimal choice for overall catalytic performance and loading content control.

[0160] This invention establishes a quantitative structure-activity relationship between structural evolution and catalytic performance, guiding the rational design of multifunctional SCR catalysts, bridging the gap between molecular mechanism understanding and engineering practice needs, and filling a key gap in the existing copper zeolite system for next-generation emission control technologies.

[0161] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. An NH3-SCR catalyst, characterized in that, The NH3-SCR catalyst comprises an LTA molecular sieve and an active component supported on the LTA molecular sieve, wherein the active component comprises Cu and rare earth metal elements.

2. The NH3-SCR catalyst according to claim 1, characterized in that, The rare earth metal element includes any one or a combination of at least two of Ce, Y, La, Pr, Nd, Sm, Gd or Yb, preferably Ce.

3. The NH3-SCR catalyst according to claim 1 or 2, characterized in that, The LTA molecular sieve has a silica-to-alumina ratio of 9 to 30.

4. The NH3-SCR catalyst according to any one of claims 1-3, characterized in that, The loading of Cu on the LTA molecular sieve is 0.5wt%~3.5wt%; Preferably, the loading of the rare earth metal elements on the LTA molecular sieve is 0.5 wt% to 10.5 wt%. Preferably, the mass ratio of Cu to rare earth metal elements is 1:(0.5~4); Preferably, the average particle size of the NH3-SCR catalyst is 2.5 μm to 3.5 μm.

5. A method for preparing the NH3-SCR catalyst according to any one of claims 1-4, characterized in that, The preparation method includes: firstly preparing an LTA molecular sieve, and then loading an active component onto the LTA molecular sieve by impregnation and / or ion exchange to obtain the NH3-SCR catalyst.

6. The preparation method according to claim 5, characterized in that, The preparation method of the LTA molecular sieve includes the dry gel hydrothermal synthesis method; Preferably, the dry gel hydrothermal synthesis method includes: mixing and reacting aqueous solutions of silicon source, aluminum source and organic template agent; after the reaction is completed, removing part of the liquid in the system to obtain a sol product; then mixing it with HF for aging reaction to obtain a gel; and finally obtaining the LTA molecular sieve after crystallization and calcination.

7. The preparation method according to claim 6, characterized in that, The organic template agent includes benzimidazole analogs and tetramethylammonium hydroxide; Preferably, the benzimidazole analogue includes hydroxyl-type 1,2-dimethyl-3-(4-methylbenzyl)imidazole or hydroxyl-type 1,2-dimethyl-3-(2-fluorobenzyl)imidazole, and more preferably hydroxyl-type 1,2-dimethyl-3-(4-methylbenzyl)imidazole; Preferably, the process of mixing the aqueous solution of the silicon source, aluminum source and organic template agent includes: first dissolving the aluminum source with an aqueous solution of a benzimidazole analog, and then sequentially adding tetramethylammonium hydroxide and the silicon source; Preferably, the sol product comprises a benzimidazole analog, tetramethylammonium hydroxide, silicon dioxide, aluminum oxide, and water; Preferably, in the sol product, the molar ratio of silicon dioxide to aluminum oxide is 9 to 30; Preferably, in the sol product, the molar ratio of benzimidazole analog, tetramethylammonium hydroxide, silicon dioxide, aluminum oxide and water is 1:(0.02~0.14):(1.5~2.5):(0.002~0.16):(4~6); Preferably, the mass ratio of the HF to the benzimidazole analog in the sol product is (0.9~1.1):

1.

8. The preparation method according to claim 6 or 7, characterized in that, Prior to the calcination, the crystallized product is sequentially separated, washed, and dried; Preferably, the crystallization is carried out in a rotating, sealed hydrothermal reactor; Preferably, the crystallization temperature is 120℃~180℃; Preferably, the crystallization time is 8 hours to 4 days; Preferably, the calcination temperature is 550℃~700℃; Preferably, the calcination holding time is 4h to 10h; Preferably, the heating rate of the calcination is 1℃ / min to 5℃ / min.

9. The preparation method according to any one of claims 6-8, characterized in that, The method for loading the active component includes: The active components are loaded simultaneously or sequentially using an impregnation method; Alternatively, the active components can be loaded simultaneously or sequentially using ion exchange. Alternatively, the active components can be loaded sequentially using impregnation and ion exchange methods; Alternatively, the active components can be loaded sequentially using ion exchange and impregnation methods; Preferably, the order of loading the active components is to first load Cu and then load the rare earth metal elements; more preferably, Cu is first loaded by ion exchange and then the rare earth metal elements are loaded by impregnation. Preferably, the impregnation method is a wet impregnation method.

10. The application of an NH3-SCR catalyst according to any one of claims 1-4 or an NH3-SCR catalyst prepared by the preparation method according to any one of claims 5-9, characterized in that, The application includes the removal of nitrogen oxides from stationary source flue gas and / or mobile source exhaust gas.